2018
DOI: 10.1111/ijac.13095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZrO2on the densification behavior and properties of Indian magnesite

Abstract: Natural magnesite is the primary source for magnesia‐based refractory materials. India has vast deposits of magnesite in Salem and Almora regions. However, due to the presence of large amount of impurities which forms low‐melting compounds at elevated temperature, its high‐temperature application is restricted. Raw magnesite was evaluated in terms of chemical analysis, differential thermal analysis, thermogravimetric analysis, and phase assemblage. Zirconia (1‐5 wt %) was added to Indian natural magnesite of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The low level of MgO at Point 2 was believed to be utilized for the cubic stabilization of ZrO 2 . [19] Moreover, for S3, as shown in Figure 5(c), the addition of corn starch evidently increased the amount of micropores compared with S2. Nevertheless, the values of closed porosity in S2 and S3 samples are similar as shown in Table III.…”
Section: Microstructurementioning
confidence: 83%
See 1 more Smart Citation
“…The low level of MgO at Point 2 was believed to be utilized for the cubic stabilization of ZrO 2 . [19] Moreover, for S3, as shown in Figure 5(c), the addition of corn starch evidently increased the amount of micropores compared with S2. Nevertheless, the values of closed porosity in S2 and S3 samples are similar as shown in Table III.…”
Section: Microstructurementioning
confidence: 83%
“…[18][19][20][21] Many previous works have proposed that the addition of ZrO 2 not only improves the sintering of magnesia aggregates by intensifying secondary liquid phase formation and promoting diffusion through vacancy creation, [18][19][20] but also enhances their mechanical strength and thermal shock resistance by adjusting their microstructure. [21,22] For instance, Ghosh et al [19] demonstrated that a 3 wt pct-addition of ZrO 2 utilized the CaO in magnesite for tetragonal stabilization, which reduced the formation of the CMS phase and improved its strength. Peng et al [21] found that ZrO 2 formed from the decomposition of added zircon reacted with MgO in magnesia to form a MgO-ZrO 2 solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ZrO 2 has a relatively high thermal conductivity with additional excellent radioactive resistance and good mechanical properties. 11,12 The tetragonal (t)-monoclinic (m) transition of zirconia is believed to easily occur at temperatures less than 1150 C. 13 This phase transition accompanying a change in the exterior environment induces a volume dilation of $4 vol%. The stresses resulting from the volumetric changes can induce crack openings and thus limit the application of zirconia.…”
Section: Introductionmentioning
confidence: 99%